Analisis Sistem Pengelolaan Dana Hibah Community Based Development Bali Sejahtera dengan Berlandaskan Kearifan Lokal Paras – Paros pada Desa Adat Giri Utama - Ni Luh Putri Cintya Dewi; I Putu Gede Diatmika (Universitas Pendidikan Ganesha, 2021)
This study aims to determine: (1) the background of the Giri Utama Traditional Village in managing the CBD-Bali Sejahtera grant funds as productive economic business credit, (2) the management system for the CBD-Bali Sejahtera grant fund based on local wisdom paras-paros in the Giri Utama Traditional Village, and (3) the obstacles faced in this system and how to solve them. This study was designed using a qualitative method. Data were collected through observation, interviews and documentation studies. The results showed that: (1) background of the Giri Utama Traditional Village manage the CBD-Bali Sejahtera grant funds as productive economic business credit, which were the difficulties experienced by the people of the Giri Utama Traditional Village in obtaining venture capital, (2) management system grants CBD-Bali Sejahtera in the Giri Utama Traditional Village consists of stages of planning, implementation, administration, reporting and accountability which are strongly based on the value of local wisdom paras-paros (3) the obstacles faced in this system are the difficulty of choosing the people who want to be used as program administrators thus causing dual positions.